Ezra Pound and the Career of Modern Criticism Professional Attention - Coyle, Michael 1957-; Preda, Roxana 1959- (Camden House, 2018)
Forty-five years after his death, and more than seventy years after his indictment for treason, Ezra Pound remains a deeply controversial figure. Today it is hard to imagine a poet sparking national debate, but Pound did just that. His receipt in 1949 of the first-ever Bollingen Award for Poetry started a hue and cry that spread to every US periodical that made even a pretense of following "cultural" issues: even Time weighed in. It took two years for things to simmer down, and when they finally did, literary study looked profoundly different. Everyone engaged in the study of poetry today, professors and students alike, works in an environment shaped by that national crisis of conscience. The present book considers this untold story, and investigates not just what critics have had to say about Pound but also why they have asked the questions they have asked. It is routine for reception histories to distinguish between professional studies and more popular responses; this book encourages us to consider why we make that distinction and what the costs of doing so might be. Unprofessional responses to Pound have often been ideologically and politically embarrassing for Pound scholars, who have in response policed the distinction between professional and popular readings with extraordinary vigilance. As a result, the history of Pound's reception unfolds as a kind of drama - perhaps the last ongoing theater for McCarthyite cultural-political anxieties. Michael Coyle is Professor of English at Colgate University and has published widely on Pound. Roxana Preda is Leverhulme Fellow in American Literature at the University of Edinburgh and President of the Ezra Pound Society
Keywords: Pound, Ezra -- 1885-1972; Geschichte 1907-2017; Rezeption